Mila = Apples [videorecording (DVD)] - Blanchett, Cate, 1969-; Raptus, Stavros; Servetalis, Aris, 1976-; Georgovassili, Sofia; Kalaitzidou, Anna; Voulgaris, Alexander; Waititi, Taika (Contemporary classics (Cohen Media Group), 2022)
Amidst a worldwide pandemic that causes sudden amnesia, middle-aged Aris finds himself enrolled in a recovery program designed to help unclaimed patients build new identities. Prescribed daily tasks on cassette tapes so he can create new memories and document them on camera, Aris slides back into ordinary life, meeting Anna, a woman who is also in recovery. Through images deadpan, strange and surreal, Greek writer-director Christos Nikou posits a beguiling reflection on memory, identity, and loss, exploring how a society might handle an irreversible epidemic through one man's story of self-discovery. Are we the sum of the images we compile and display of ourselves, or are we something richer, and deeper? --